2020
DOI: 10.1039/d0dt00665c
|View full text |Cite
|
Sign up to set email alerts
|

Allene-derived gold and platinum complexes: synthesis and first applications in catalysis

Abstract: Novel metal carbene complexes made from bis(pyridyl)allenes have promising catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…Attempts to improve the efficiency of the reaction, for example, by increasing the temperature, resulted in full conversion into the cyclic product 5a, observed in our previous work. 28 On the other hand, reaction of 1b in refluxing methanol yielded a mixture of allene-containing complex 4b and mixture of isomers of the cyclised 5b that could be easily separated afterwards, as previously reported. 28 Characterisation of 4a-b confirmed the presence of the allene moiety and the N,N-chelating character of these complexes.…”
Section: Synthesis Of Bis( Pyridyl)allene Metal Complexessupporting
confidence: 64%
See 3 more Smart Citations
“…Attempts to improve the efficiency of the reaction, for example, by increasing the temperature, resulted in full conversion into the cyclic product 5a, observed in our previous work. 28 On the other hand, reaction of 1b in refluxing methanol yielded a mixture of allene-containing complex 4b and mixture of isomers of the cyclised 5b that could be easily separated afterwards, as previously reported. 28 Characterisation of 4a-b confirmed the presence of the allene moiety and the N,N-chelating character of these complexes.…”
Section: Synthesis Of Bis( Pyridyl)allene Metal Complexessupporting
confidence: 64%
“…The more reactive 3b underwent cycloplatination under reducing conditions losing the allene core in the process. 28 Inertness of 3ab under milder reduction conditions might be explained by their quite negative Pt(IV)/Pt(II) reduction potentials found at −1.0 V and −1.1 V, respectively for 3a and 3b, as measured by cyclic voltammetry of these complexes (see ESI, † section 2.2).…”
Section: Synthesis Of Bis( Pyridyl)allene Metal Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gold complexes of carbenes lacking this heteroatom stabilization have been reported only recently. 16 The groups of Fensterbank 17 and Munoz 18 reported that cycloisomerization of allenylpyridines allows the isolation of gold and platinum complexes of indolizin-2-ylidene (Indolizy) type carbenes, that is carbenes with the heteroatom in 3position relative to the carbene-C. 19 Here we report new Indolizy carbene gold complexes having chloride and carbazolide anionic ligands in order to study the effect of carbenes with remote heteroatom stabilization on the photoluminescent properties of the CMA materials.…”
Section: Introductionmentioning
confidence: 97%